Interpretation of History in the Contemporary Lithuanian Essayistics - Meržvinskaitė, Birutė (Literatūra, 2021)
The article discusses the peculiarities of the representation of history in Sigitas Parulskis’s essay collection Eternity does not move me (2018). The essay as genre in this book unites subjectivity, critical and ironic mode of narration and the conventional categories of historiographical analysis (the state, religion, society, collective identity, culture). Explanation on the ambivalent sense and relationship between literary imagination and historical facticity is done to prove the New Historicism slogan “the historicity of texts and the textuality of history”.
Keywords: history; essay; textuality; mythos; identity; trauma